2005
DOI: 10.1111/j.1365-2958.2005.04850.x
|View full text |Cite
|
Sign up to set email alerts
|

Variant proteins of Plasmodium vivax are not clonally expressed in natural infections

Abstract: SummaryPlasmodium vivax is the most widely distributed human malaria parasite and responsible for 70-80 million clinical cases each year and a large socioeconomical burden. The sequence of a chromosome end from P. vivax revealed the existence of a multigene superfamily, termed vir ( P. vivax variant antigens), that can be subdivided into different subfamilies based on sequence similarity analysis and which represents close to 10-20% of the coding sequences of the parasite. Here we show that there is a vast rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
56
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 35 publications
11
56
1
Order By: Relevance
“…This may be partly explained by the limited conservation of known proteins associated with the P. falciparum trafficking machinery in other Plasmodium species (58). In addition, there has been only limited success in setting up short-term culture systems to support such basic studies of P. vivax (57,(59)(60)(61). However, it has not been shown if the transport machinery utilized by P. vivax is unique or if the reticulocyte cytoplasm influences export.…”
Section: Discussionmentioning
confidence: 99%
“…This may be partly explained by the limited conservation of known proteins associated with the P. falciparum trafficking machinery in other Plasmodium species (58). In addition, there has been only limited success in setting up short-term culture systems to support such basic studies of P. vivax (57,(59)(60)(61). However, it has not been shown if the transport machinery utilized by P. vivax is unique or if the reticulocyte cytoplasm influences export.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez-Becerra et al (39) has shown that in natural infections, P. vivax isolates express ''large and mostly nonoverlapping'' vir gene repertoires. This phenomenon was attributed mainly to the extensive polymorphisms detected in the vir gene family.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the function of vir genes is probably not directly related to the antigenic variations in the strict sense (del Portillo et al 2004). The fact that not all their proteins are exported to the surface of infected red blood cells (Fernandez-Becerra et al 2005) reinforces the idea that vir genes may have different functions related to immune evasion (Merino et al 2006). The acquired immune responses to P. vivax variant antigens were also evaluated in individuals living in Brazilian malaria-endemic areas.…”
Section: Vir Genesmentioning
confidence: 84%
“…Despite the limited availability of P. vivax biological material, recent research has led to the construction of P. vivax genome in yeast artificial chromosomes (YAC). This new tool has revolutionized studies on the structure and function of the P. vivax genome, with the search of new polymorphic molecular markers (Camargo et al 1997, Merino et al 2003, Feng et al 2003, Gomez et al 2003, Fernandez-Becerra et al 2005. Moreover, the availability of the P. vivax telomeric YAC clones has helped in the identification of many antigen-encoding genes mapped to the dynamic subtelomeric domains of plasmodial chromosomes; this fact has led to a suggestion that the recombination within these domains has been recruited as a novel mechanism to generate antigenic diversity (Camargo et al 1997).…”
Section: New Tools For Studies Of the P Vivax Genomementioning
confidence: 99%